2016
DOI: 10.1111/ecc.12459
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between smoking and CYP1A1 MspI polymorphism on lung cancer: a meta-analysis in the Chinese population

Abstract: Many studies have examined the interaction between CYP1A1 MspI gene polymorphism and smoking for the risk of lung cancer risk in Chinese, but their results have been inconsistent. Therefore, a meta-analysis was performed to ascertain this issue. PubMed, Springer Link, Ovid and other Chinese databases were searched to include all the relevant studies. Smoking status was categorised as 'smokers' and 'non-smokers.' The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using fixed or ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Smoking is an important risk factor for the occurrence of lung cancer. The age at which smoking starts, the daily amount of smoking, the depth of smoking, the duration of smoking, the total amount of smoking, and the time of smoking cessation are all related to the risk of developing lung cancer [8] . Studies have shown that the proportion of men among lung cancer smokers is higher, and the most common pathological type is squamous cell carcinoma, often accompanied by chronic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is an important risk factor for the occurrence of lung cancer. The age at which smoking starts, the daily amount of smoking, the depth of smoking, the duration of smoking, the total amount of smoking, and the time of smoking cessation are all related to the risk of developing lung cancer [8] . Studies have shown that the proportion of men among lung cancer smokers is higher, and the most common pathological type is squamous cell carcinoma, often accompanied by chronic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the prevalence of NSCLC has been increasing rapidly in the past few decades, and it is reported that 652,842 new patients were diagnosed in 2012 (2). A large number of epidemiological studies have confirmed that environmental factors, especially tobacco smoking and heavy alcohol drinking are associated with the risk of NSCLC (3,4). Recently, an increasing amount of studies have revealed that hereditary factors play a crucial role in susceptibility to NSCLC (5,6).…”
Section: Introductionmentioning
confidence: 99%